Phenotypic presentation of chronic cough in children - Kantar, Ahmad (Journal of Thoracic Disease, 2017)
Chronic cough in children is increasingly defined as a cough that lasts more than four weeks. It is recognized as a different entity than cough in adults. As a result, the diagnostic approach and management of chronic cough in children are no longer extrapolated from adult guidelines. These differences are attributed to the various characteristics of the respiratory tract, immunological system and nervous system in children. Specific paediatric guidelines and algorithms for chronic cough are now widely applied. Post-infectious cough, asthma, bronchiectasis, malacia and protracted bacterial bronchitis (PBB) appear to be the major causes of cough in young children. By adolescence, the causes of cough are more likely to be similar to those in adults, namely, gastroesophageal reflux, asthma, and upper airway syndrome. In a primary setting, it is essential to investigate the underlying disease entity that initiates and sustains chronic cough. The use of cough management protocols or algorithms improves clinical outcomes and should differ depending on the associated characteristics of the cough and the child’s clinical history. Performing a thorough history and physical examination is crucial to starting an individualised approach. A correct interpretation of the phenotypic presentation can be translated into guidance for workup. This approach will be helpful for adequate management without the risk of inappropriate investigations or inadequate treatment.